Gender, household behavior, and rural development - Doss, Cheryl; Quisumbing, Agnes R. (International Food Policy Research Institute, 2018)
This paper reviews recent conceptual and empirical developments regarding household behavior and gender norms in developing countries covering the following general topics: (1) what do the data tell us about gender gaps in control and ownership of resources? (2) what have we learned about jointness in household behavior; (3) what do the data tell us about the resources that men and women control, whether solely or jointly; and (4) why does it matter?